2021
DOI: 10.1108/ijqrm-01-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

Lean Six Sigma and Assurance of Learning (AoL) in higher education: a case study

Abstract: PurposeThis study aims to present a case study using a Lean Six Sigma (LSS) process to manage the Assurance of Learning (AoL) process in higher education. The case study highlights the value that LSS can bring to the higher education context in respect to making the AoL process more efficient and more effective. The article also illustrates lessons learned in relation to adopting LSS in higher education institutes (HEIs).Design/methodology/approachThe case study presented is part of a larger undertaking implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…, 2022). Literature reveals that LSS is an efficient continuous improvement approach adopted in various real-life applications (Adeinat et al. , 2022).…”
Section: Discussion On Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022). Literature reveals that LSS is an efficient continuous improvement approach adopted in various real-life applications (Adeinat et al. , 2022).…”
Section: Discussion On Findingsmentioning
confidence: 99%
“…(Bhat et al, 2022). Literature reveals that LSS is an efficient continuous improvement approach adopted in various real-life applications (Adeinat et al, 2022). But the implementation of LSS in the healthcare sector is at the initial stage due to a lack of awareness about the success factor and barriers of LSS, poor availability of implementation framework, etc.…”
Section: Discussion On Findingsmentioning
confidence: 99%
“…Additionally, it aims at predicting process variation, productivity and process capability of three assessment methods (quiz, assignment and the final examination) for a first-year undergraduate Quality Management System course at School of Technology Management and Logistics with a total of 50 students involved. Adeinat et al (2022) describe an approach for using Six Sigma combined with Lean Management (LSS) to manage AoL in the domain of higher education. Their experiences were that Six Sigma can bring a clear added value with regards to AoL effectiveness and efficiency and highlighted three success factors for LSS: clear responsibility of the stakeholders, a common language for LSS within the cross-disciplinary team to foster collaboration and definition of quantifiable priorities.…”
Section: Aol Implementations At Other Universitiesmentioning
confidence: 99%
“…The DMAIC cycle is very similar to the classical PDCA approach, however, especially for the "M" and "A", a considerable number of proven mathematical and statistical methods are available in the Six Sigma toolbox. As described in the approach of Adeinat et al (2022), Six Sigma is often extended to Lean Six Sigma (LSS). LSS implies the usage of lean management techniques (i.e.…”
mentioning
confidence: 99%
“…The positive impact of LSS implementation is evident in successful case studies. For instance, Stanton et al (2014) demonstrated improved flow in hospital emergency departments, Noronha et al (2021) showcased enhanced performance and service quality in healthcare sectors and Adeinat et al (2022) highlighted increased efficiency within higher education processes. To exemplify further, Cournoyer et al (2013) applied LSS to enhance business practices related to air-purifying respirators, resulting in improved efficiency, streamlined operations and cost-effectiveness that met the specific requirements of nuclear research personnel.…”
Section: Introductionmentioning
confidence: 99%